Analysis and Modulation of PACT, DICER and MBNL1 in the Context of Myotonic Dystrophy Type I - Azimi, Mehrdad (Université d'Ottawa / University of Ottawa, 2016)
Myotonic Dystrophy Type I (DM1) is a multi-systemic genetic neuromuscular degenerative disease, has a prevalence in most populations of about 1:8000 and is caused by the nuclear retention of pathogenically expanded DMPK mRNA. A previous DM1 RNAi-kinome screen in our lab has identified kinases that reduced both count and area of DMPK mRNA foci in vitro. One such discovered kinase is PACT, which has showed to decrease foci count and area in DM1 fibroblasts by 30-50%. This study explored PACT as well as binding partner DICER involved in cellular RNA processing machinery, to highlight potential therapeutic targets in DM1. DM1 fibroblasts treated with PACT siRNA showed a non-significant trend of upregulation in MBNL1 mRNA and protein expression. PACT knockdown also showed trend of missplicing normalization in SERCA-1, more prominently seen in DM1-2000 human fibroblasts, whereas IR (insulin receptor) splicing remained unaffected. On the other hand, DICER knockdown did not have profound affect on foci integrity as well as MBNL1 RNA and protein xpressions in DM1 fibroblasts. SERCA-1 splicing in DICER siRNA treated samples also remained unchanged. We report here our findings in pursuit of potential therapeutic targets for the treatment of DM1.
Keywords: Myotonic Dystrophy Type I; DM1; PACT; DICER; TRBP; miRNA; PKR; Alternative splicing; Nuclear foci; MBNL1; DMPK; SERCA1; Insulin receptor; RISC